Przestępstwa seksualne wobec małoletnich w świetle znowelizowanej księgi VI Kodeksu Prawa Kanonicznego - Dariusz Mazurkiewicz (Studia Paradyskie, 2023)
Due to the appearing accusations against some clergymen of sexual abuse of minors, the church legislator has been consistently tightening the canonical criminal law for many years. The purpose of this action is to ensure the protection of children and young people. This is done in three areas. The first is building preventive systems, the second is the promulgation of substantive penal norms, the third is the creation of a lex specialis on the basis of the existing formal law on procedures aimed at punishing perpetrators, and thus redressing the scandal and compensating for the violated justice. Penal material norms play an important role in the entire system of protection of minors. The most recent amendment to the Code of Canon Law listed sexual offenses committed against minors and their equated persons as acts against human life, dignity and freedom, and therefore considered them the most serious canonical offenses. Basing on the earlier norms, the church legislator first criminalized the broadly understood sexual acts committed against these people, further defined as criminal activities aimed at seducing or persuading them to present themselves in pornographic scenes, and finally included the broadly understood acquisition, storage, presentation and disseminating pornography with images of minors. The definition of these crimes is often broader than in state legislation. Additionally, in the last amendment, the legislator extended the concept of an entity capable of committing this type of crime. Thus, another amendment to the canon law increased the scope of protection for minors and their equated persons